2018
DOI: 10.1039/c8dt00955d
|View full text |Cite
|
Sign up to set email alerts
|

Viologen-modified electrodes for protection of hydrogenases from high potential inactivation while performing H2oxidation at low overpotential

Abstract: In this work we present a viologen-modified electrode providing protection for hydrogenases against high potential inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Various ligands were synthesized to tune the redox potentials of the hydrogels. 593 A similar viologen polymer-modified bioelectrode has been reported by Kano's group for formate oxidation by FDH, and a formate/O 2 EFC with an OCV of 1.2 V was recorded. 15 Compared to the DET-type bioelectrocatalysis and MET-type bioelectrocatalysis using free mediators, redox polymer-based bioelectrocatalysis possess advantages such as rapid rates of ET, low levels of mediators and/or enzyme leakage.…”
Section: Chemical Reviewssupporting
confidence: 64%
See 1 more Smart Citation
“…Various ligands were synthesized to tune the redox potentials of the hydrogels. 593 A similar viologen polymer-modified bioelectrode has been reported by Kano's group for formate oxidation by FDH, and a formate/O 2 EFC with an OCV of 1.2 V was recorded. 15 Compared to the DET-type bioelectrocatalysis and MET-type bioelectrocatalysis using free mediators, redox polymer-based bioelectrocatalysis possess advantages such as rapid rates of ET, low levels of mediators and/or enzyme leakage.…”
Section: Chemical Reviewssupporting
confidence: 64%
“… H 2 /O 2 EFCs with high OCVs of ∼1 V were fabricated by combination of such viologen-based polymer MET-type H 2 bioanodes and DET-type O 2 biocathodes. Various ligands were synthesized to tune the redox potentials of the hydrogels . A similar viologen polymer-modified bioelectrode has been reported by Kano’s group for formate oxidation by FDH, and a formate/O 2 EFC with an OCV of 1.2 V was recorded .…”
Section: Approaches For the Improvement Of Efcs’ Cell Voltagementioning
confidence: 95%
“…In addition, redox polymers can serve as a protection against oxygen for oxygen-sensitive enzymes, , unwanted contributions from DET of contaminants, and high potential deactivations, that are limiting factors in further improving enzyme-based applications . Specifically, Szczesny et al built a bioanode using the viologen-modified redox polymers to mediate hydrogenase .…”
Section: The Bioelectrocatalysis Systemmentioning
confidence: 99%
“…Alternatively, it was shown that embedding the hydrogenase in a viologen-based hydrogel protected the enzyme from high potential deactivation. In this MET process, the enzyme no longer senses the high potential of the electrode but the potential of the viologen redox couple which is sufficiently negative to prevent HASE inactivation [287][288][289]. Nevertheless, the use of redox mediators induces other detrimental effects towards enzyme stability, such as production of reactive oxygen species (ROS) that will be discussed in the next section.…”
Section: Effect Of the Electric Fieldmentioning
confidence: 99%